Unbalanced multiple description video communication using path diversity - Apostolopoulos, J.G.; Wee, S.J. (2001 International Conference on Image Processing, 2001)
Multiple description (MD) coders provide important error resilience properties. Specifically, MD coders are designed to provide good performance when the loss is limited to a single description, but it is not known in advance which description. Apostolopoulos (2001) combined MD video coding with a path diversity transmission system for packet networks such as the Internet, where different descriptions are explicitly transmitted through different network paths, to improve the effectiveness of MD coding over a packet network by increasing the likelihood that the loss probabilities for each description are independent. The available bandwidth in each path may be similar or different, resulting in the requirement of balanced or unbalanced operation, where the bit rate of each description may differ based on the available bandwidth along its path. We design a MD video communication system that is effective in both balanced and unbalanced operation. Specifically, unbalanced MD streams are created by carefully adjusting the frame rate of each description, thereby achieving unbalanced rates of almost 2:1 while preserving MD's effectiveness and error recovery capability.